Investigation of novel bis-thiadiazole bearing schiff base derivatives as effective inhibitors of thymidine phosphorylase: Synthesis, in vitro bioactivity and molecular docking study - Rafaqat Hussain; Wajid Rehman; Shoaib Khan; Fadi Jaber; Fazal Rahim; Mazloom Shah; Yousaf Khan; Shahid Iqbal; Haseena Naz; Imran Khan; Mohammed Issa Alahmdi; Nasser S. Awwad; et al. (Elsevier, 2023)
Thymidine phosphorylase (TP) is an angiogenic enzyme. It is crucial for the development, invasion and metastasis of tumors as well as angiogenesis. In our current research, we examine how structurally changing bis-thiadiazole bearing bis-schiff bases affects their ability to inhibit TP. Through the oxidative cyclization of pyridine-based bis-thiosemicarbazone with iodine, a series of fourteen analogs of bis-thiadiazole-based bis-imines with pyridine moiety were developed. Newly synthesized scaffolds were assessed in vitro for their thymidine phosphorylase inhibitory potential and showed moderate to good inhibition profile. Eleven scaffolds such as 4a-4d,4f-4 h and 4j-4 m were discovered to be more effective than standard drug at inhibiting the thymidine phosphorylase enzyme with IC50 values of 1.16 ± 1.20, 1.77 ± 1.10, 2.48 ± 1.30, 12.54 ± 1.60, 14.63 ± 1.70, 15.53 ± 1.80, 17.47 ± 1.70, 18.98 ± 1.70, 19.53 ± 1.50, 22.73 ± 2.40 and 24.87 ± 2.80 respectively, while remaining three analogs such as 4n, 4i and 4ewere found to be more potent, but they were less potent than the standard drug. All analogs underwent SAR studies based on the pattern of substitutions around the aryl part of the bis-thiadiazole skeleton. The most active analogs in the synthesized series were then molecular docking study performed to investigate their interactions of active part of enzyme. The results showed that remarkable interactions were exhibited by these analogs with the targeted enzymes active sites. Furthermore, to confirm the structure of synthesized analogs by employing spectroscopic tools such as HREI-MS and NMR.